Recurrent cementoblastoma with multifocal growth and cellular atypia: a case report - Kaori Oya; Akinori Takeshita; Kanta Wakamori; Misa Song; Hayato Kimura; Katsutoshi Hirose; Hiroaki Shimamoto; Sunao Sato; Kazuhide Matsunaga; Narikazu Uzawa; Satoru Toyosawa (Diagnostic Pathology, 2024)
Abstract Background Cementoblastoma is a rare odontogenic tumor characterized by the formation of osteocementum-like tissue on a tooth root directly by neoplastic cementoblasts. Although it is categorized as benign, it has a high potential for growth with a certain degree of recurrence risk. However, there are only a few studies describing the features of recurrent cementoblastoma. The diagnosis of recurrent cementoblastoma is challenging not only due to its cytological atypia but also because of its large size and multicentric growth pattern. These characteristics suggest a potential for malignancy. Case presentation A 29-year-old woman was transferred to our university dental hospital complaining of swelling of the right mandible. She had a history of enucleation of cementoblastoma associated with the third molar of the right mandible. Five years after the initial treatment, imaging demonstrated well-circumscribed multicentric radiopaque lesions in the same area. Histologically, the lesion consisted of osteocementum-like tissue rimmed with polygonal or plump tumor cells. Several cells were large epithelioid cells with bizarre nucleoli, which may be reminiscent of malignant tumors. Otherwise, there were no apparent malignant findings, including proliferative activity or atypical mitotic figure. Besides, tumor cells were positive for c-FOS, a marker of osteoblastoma and cementoblastoma. Eventually, the patient was diagnosed with recurrent cementoblastoma. Conclusions Pathological analyses of this case suggested that the recurrent event in the cementoblastoma altered its growth pattern and tumor cell shape. Moreover, in the case of enucleation surgery, long-term follow-up is important because there is some recurrent risk of cementoblastoma, although it is not high.